Insulating material partial discharge intensity detection experiment system and method under non-uniform electric field
Patent Information
- Application Number
- CN202611021601.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-09
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]针对绝缘材料在机械应力作用下的电气响应行为,现有技术从不同角度揭示了机械载荷对电树枝生长及击穿强度的调制作用,但研究对象多集中于强非均匀场条件下的电树枝或击穿过程,对于电气设备中更为常见的空腔型局部放电模型,机械应力的影响规律仍缺乏研究
(1)本发明构建稳定的电–热–力三场耦合加载架构,并在局部放电检测过程中引入介电参数测量、表面电位衰减监测以及微观形貌获取;不仅在宏观上实现试样在固定位置、固定电极间距及固定应力状态下的连续局放测量,避免了传统“卸载—再夹持”导致的气隙重构与电场畸变;更从微观物理机制层面,通过原位获取材料在应力作用下的复介电常数变化与表面电位衰减(SPD)特性,揭示机械应力通过改变材料微观结构(如自由体积、微裂纹)、介电响应及陷阱能级分布,进而调控气隙内部残余场强与击穿阈值的物理机制。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of discharge detection technology for insulating materials, and in particular to an experimental system and method for detecting the partial discharge intensity of insulating materials under a non-uniform electric field. Background Technology
[0002] The statements in this section are merely background information related to the present invention and do not necessarily constitute prior art.
[0003] Partial discharge (PD) is a key technology for assessing and diagnosing the insulation condition of high-voltage electrical equipment. Although partial discharge is weak, its long-term presence will continuously corrode the insulation material, causing electrical erosion, thermal aging, and chemical decomposition, ultimately leading to a decline in insulation performance and even sudden equipment failure or breakdown.
[0004] For example, epoxy resin, due to its excellent structural stability and electrical insulation properties, is widely used in solid-insulation structures such as ultra-high voltage reactors, instrument transformers, and GIS bushings. However, the epoxy system undergoes volume shrinkage during the curing reaction. Simultaneously, due to uneven thermal fields and interfacial mismatches during operation, internal stress easily leads to structural defects such as microcracks and delamination, which can induce partial discharge and electrical breakdown. Existing research indicates that when the internal stress of epoxy exceeds 2–10 MPa, it may trigger electric field distortion, becoming a source of partial discharge.
[0005] Regarding the electrical response behavior of insulating materials under mechanical stress, existing technologies have revealed the modulating effect of mechanical load on electrical tree growth and breakdown strength from different perspectives. However, most studies focus on electrical trees or breakdown processes under strong non-uniform field conditions. For the cavity-type partial discharge model, which is more common in electrical equipment, the influence of mechanical stress is still lacking.
[0006] Furthermore, existing studies mostly focus on macroscopic discharge characteristics, and the coupling relationship between the stress-strain response of materials and their microscopic morphology evolution and electrical behavior has not been fully revealed. Since stress and strain-induced microscopic defects and interface state changes modulate carrier injection, trap distribution, and surface charge dissipation paths, if the force-electric coupling effect is ignored, partial discharge models often assume that electrical parameters are constant, which cannot reflect the dynamic evolution of charge accumulation and release under actual operating conditions, causing the predicted results to deviate from the actual discharge intensity. Summary of the Invention
[0007] To address the aforementioned issues, this invention proposes an experimental system and method for detecting partial discharge intensity in insulating materials under non-uniform electric fields. It constructs a loading architecture that couples the electric, thermal, and mechanical fields, and obtains in-situ the changes in the complex permittivity and surface potential decay (SPD) characteristics of the material under stress. Combined with real-time observation information of partial discharge events, it achieves accurate modeling of the evolution law of partial discharge, thereby enabling precise prediction of the development trend and risk state of partial discharge in insulating materials under complex service environments.
[0008] In some implementations, the following technical solutions are adopted: An experimental system for detecting the partial discharge intensity of insulating materials under a non-uniform electric field includes: The three-field coupling loading module is used to apply controllable tensile or compressive stress to the test specimen and simultaneously introduce electric and temperature fields to put the test specimen in a stable and reproducible force-thermal-electric coupling constraint state. The partial discharge detection module is used to collect the partial discharge current signal of the test sample to characterize the occurrence time and intensity characteristics of the partial discharge event, and transmit it to the main control module. The in-situ dielectric spectroscopy testing module is used to measure the complex dielectric constant of the test sample under stress and transmit it to the main control module. The surface potential decay monitoring module is used to inject a quantitative charge into the surface of the test sample under stress and record the decay curve of the surface potential of the test sample in situ to extract the stress-related charge decay time constant and transmit it to the main control module. The micromorphology acquisition module is used to acquire the crack initiation and propagation path of the test specimen under stress in real time and transmit it to the main control module. The main control module is used to receive data uploaded by each module and establish the physical correlation between microstructure, complex dielectric constant, charge decay time constant and partial discharge response under stress, so as to achieve accurate prediction of the partial discharge risk of insulating materials in complex service environments.
[0009] Specifically, the three-field coupling loading module includes: The mechanical loading unit includes insulating clamps for holding both ends of the test specimen, and a push-pull force gauge connected to at least one insulating clamp; the push-pull force gauge applies in-situ mechanical tensile or compressive stress to the test specimen to simulate the residual or service stress state of the test specimen in actual equipment caused by structural constraints, curing shrinkage or operating loads. Temperature control unit, including an electrothermal aging chamber, is used to provide a preset temperature environment for the test sample; The electric field generating unit includes ball-plate electrodes respectively disposed on the upper and lower end faces of the test specimen, which are used to provide a controllable non-uniform electric field for the test specimen.
[0010] In other embodiments, the following technical solutions are adopted: An experimental method for detecting the partial discharge intensity of insulating materials under a non-uniform electric field includes: A controllable tensile or compressive stress is applied to the test specimen, and an electric field and a temperature field are introduced simultaneously to put the test specimen in a stable and reproducible force-thermal-electric coupling constraint state. The complex permittivity, surface potential decay curve, crack initiation and propagation path, and partial discharge current signal of the test specimen under stress were measured respectively to establish the physical relationship between microstructure, complex permittivity, charge decay time constant and partial discharge response under stress. Based on the aforementioned physical correlation, accurate prediction of the partial discharge risk of insulating material test samples under complex service environments can be achieved.
[0011] Compared with the prior art, the beneficial effects of the present invention are: (1) This invention constructs a stable electro-thermal-mechanical three-field coupled loading architecture and introduces dielectric parameter measurement, surface potential decay monitoring and micromorphology acquisition in the partial discharge detection process; it not only realizes continuous partial discharge measurement of the sample in a fixed position, fixed electrode spacing and fixed stress state on a macroscopic level, avoiding the air gap reconstruction and electric field distortion caused by the traditional "unloading-re-clamping"; but also reveals the physical mechanism of mechanical stress by obtaining the change of complex dielectric constant and surface potential decay (SPD) characteristics of the material under stress in situ at the level of microphysical mechanism, thereby controlling the residual field strength and breakdown threshold inside the air gap by changing the material microstructure (such as free volume, microcracks), dielectric response and trap energy level distribution.
[0012] (2) From the perspective of electrical insulation, lifetime is not a single breakdown, but the accumulation of partial discharge energy over time, leading to irreversible growth of microstructural damage and ultimately causing macroscopic failure. This invention reveals the synergistic regulation mechanism of mechanical stress on the electrical state and discharge behavior of insulating materials by establishing the physical correlation between micromorphology, complex permittivity, charge decay time constant, and partial discharge response, and constructs a quantitative mapping relationship that can characterize the stress inflection point effect. This mapping relationship transforms the partial discharge intensity from a single signal representation into a function of the material state, thereby identifying the characteristic stress points where the insulating material transitions from a stable service area to a rapid degradation area. By transforming partial discharge from a "result signal" into a "function of the material state," the discharge intensity, probability of occurrence, and evolution trend can be forward calculated and predicted. Based on this, a correspondence can be established between partial discharge intensity and degradation rate, thereby realizing lifetime assessment and structural optimization design of insulating materials under complex stress conditions.
[0013] Other features and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Attached Figure Description
[0014] Figure 1 This is a schematic diagram of the experimental system for detecting the partial discharge intensity of insulating materials under a non-uniform electric field, as described in an embodiment of the present invention. Figure 2 This is a flowchart of the experimental method for detecting the partial discharge intensity of insulating materials under a non-uniform electric field in an embodiment of the present invention; Figure 3 The figures show the relationship between the discharge amplitude and the number of discharges for EP-AFD and EP-MDA under different stress levels and temperatures in the embodiments of the present invention; wherein, (a) is the relationship curve of the discharge amplitude and (b) is the relationship curve of the number of discharges. Figure 4 This is a schematic diagram illustrating the skewness and kurtosis analysis of the discharge amplitude distribution of EP-AFD and EP-MDA under different stress levels and temperatures in an embodiment of the present invention. Figure 5 The images show the PRPD spectra of EP-AFD at 20°C and different stress levels in the embodiments of the present invention; wherein, (a) is the PRPD spectrum at 20°C and 0 MPa, (b) is the PRPD spectrum at 20°C and 10 MPa, and (c) is the PRPD spectrum at 20°C and 20 MPa. Figure 6 The images show the PRPD spectra of EP-AFD at 70°C and different stress levels in the embodiments of the present invention; wherein, (a) is the PRPD spectrum at 70°C and 0 MPa, (b) is the PRPD spectrum at 70°C and 10 MPa, and (c) is the PRPD spectrum at 70°C and 20 MPa. Figure 7 The images show the PRPD spectra of EP-MDA at 20°C and different stress levels in the embodiments of the present invention; wherein, (a) is the PRPD spectrum at 20°C and 0 MPa, (b) is the PRPD spectrum at 20°C and 10 MPa, and (c) is the PRPD spectrum at 20°C and 20 MPa. Figure 8 The images show the PRPD spectra of EP-MDA at 70°C and different stress levels in the embodiments of the present invention; wherein, (a) is the PRPD spectrum at 70°C and 0 MPa, (b) is the PRPD spectrum at 70°C and 10 MPa, and (c) is the PRPD spectrum at 70°C and 20 MPa. Figure 9 These are SEM images under different stress conditions in embodiments of the present invention; Figure 10 These are the test results of the dielectric constant and dielectric loss factor of the EP-AFD under different stresses in the embodiments of the present invention; Figure 11 The results of the dielectric constant and dielectric loss factor of EP-MDA under different stress conditions in the embodiments of the present invention are shown. Figure 12 This is a schematic diagram of the surface potential change of EP-AFD under different stresses in an embodiment of the present invention; Figure 13 This is a schematic diagram of the surface potential change of EP-MDA under different stresses in an embodiment of the present invention; Figure 14 This is a schematic diagram illustrating the evolution of the epoxy resin structure under increased stress in an embodiment of the present invention; Figure 15 This is a schematic diagram of the electric field distribution at the three-point junction in an embodiment of the present invention; Figure 16 This is a schematic diagram of charge behavior during the polarity reversal of an applied voltage in an embodiment of the present invention; Figure 17 This is a schematic diagram of the electric field distribution at the defect location in an embodiment of the present invention; Figure 18 This is a schematic diagram of the electric field distribution on the surface of the epoxy resin film in an embodiment of the present invention. Detailed Implementation
[0015] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0016] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0017] Example 1 First, it should be noted that the insulating material in this embodiment is not limited to epoxy resin film or bulk material. In principle, it is applicable to solid / composite insulating media that may generate micro-defects and induce partial discharge under the combined action of high electric field, temperature gradient and mechanical stress. The range of optional materials includes, but is not limited to: thermosetting resin insulating materials, bisphenol A type epoxy (DGEBA / BADGE) and its modified systems (including flexible segments, toughening agents, dynamic bond networks, nanofiller modification, etc.), epoxy castings / solid-sealed insulating materials (reactors, transformers, GIS solid-sealed pole / post insulation, etc.), unsaturated polyester, vinyl ester and other similar thermosetting insulating resins.
[0018] In one or more embodiments, an experimental system for detecting the partial discharge intensity of insulating materials under a non-uniform electric field is disclosed, combined with Figure 1 Specifically, it includes: (1) Three-field coupling loading module, used to apply controllable tensile or compressive stress to the test specimen and simultaneously introduce electric and temperature fields to make the test specimen in a stable and reproducible force-thermal-electric coupling constraint state.
[0019] Specifically, the three-field coupled loading module includes: (1-1) Mechanical loading unit, including insulating clamps for holding the two ends of the insulating material test specimen, and a push-pull force gauge connected to at least one insulating clamp; applying in-situ mechanical tensile or compressive stress to the test specimen through the push-pull force gauge to simulate the residual or service stress state of the test specimen in actual equipment caused by structural constraints, curing shrinkage or operating load.
[0020] (1-2) Temperature control unit, including an electric heating aging chamber, for providing a preset temperature environment for the test sample.
[0021] (1-3) Electric field generation unit, including ball-plate electrodes respectively disposed on the upper and lower end faces of the test sample, for providing a controllable non-uniform electric field for the test sample.
[0022] In a specific implementation, the push-pull force gauge is connected to one of the insulating clamps via an insulating pull rod, while the other insulating clamp is fixedly installed. The two insulating clamps are symmetrically clamped at both ends of the test specimen. A stepper motor drives one of the push-pull force gauges to apply tensile or compressive stress to the insulating clamp at a set rate, thereby causing the test specimen to generate stable and controllable uniaxial tensile or compressive stress in the in-plane direction. The stress magnitude is recorded in real time by the program to ensure that the specimen maintains constant mechanical boundary conditions throughout the test.
[0023] The electrodes and sample assembly are placed inside an electrothermal aging chamber, which can suppress environmental interference and external discharge; the electrothermal aging chamber can provide a precisely adjustable temperature field from 20℃ to 200℃. A controllable non-uniform electric field is generated using ball-plate electrodes, and the electrode spacing is monitored synchronously with stress loading to continuously correct the electric field calculation.
[0024] As a specific example, insulating materials with a thickness of 0.5 to 2 mm are selected and cut into sheet-like or dumbbell-shaped samples of 20 mm × 20 mm. After removing adsorbed water by vacuum drying at 80 ℃ for 12 h, the samples are naturally cooled to room temperature for later use. The pretreated samples are not clamped again during the entire test process to ensure that the discharge characteristics are compared in situ under consistent boundary conditions.
[0025] In this embodiment, in-situ measurement refers to testing under different mechanical stress levels, temperature conditions, and applied voltage stages, where the sample is not removed from the electrode clamp, nor is the electrode and sample repositioned. This ensures that the electrode spacing, contact position, and air gap morphology remain unchanged, avoiding air gap reconstruction, electric field distribution changes, and discharge initiation condition drift caused by re-clamping. Simultaneously, the stress can be adjusted or maintained according to a set value during mechanical loading, but stress changes are not achieved through unloading and re-clamping. The technical objective is to ensure the comparability and continuity of partial discharge signals obtained under different operating conditions, ensuring that changes in discharge characteristics primarily originate from changes in mechanical stress and temperature conditions, rather than from non-intrinsic factors such as clamping errors, interface contact changes, or electrode position offsets. This enables in-situ comparison and evolution analysis of partial discharge behavior under consistent boundary conditions.
[0026] The pretreated specimen is symmetrically clamped in a ball-plate electrode fixture, and a predetermined uniaxial tensile or compressive load is applied using a push-pull force gauge, with a load range of 0–5000 N. The load value is read in real time, and the corresponding average mechanical stress is calculated based on the effective cross-sectional area of the specimen. σ : ; Where F is the applied mechanical stress and S is the cross-sectional area of the material.
[0027] Simultaneously, the changes in sample thickness and electrode spacing under each stress level are recorded for subsequent electric field distribution correction.
[0028] Throughout the partial discharge test, the set tensile / compressive stress was kept constant, and the sample was not unloaded or re-clamped to ensure that the partial discharge behavior was observed in situ under continuous and stable service stress constraints.
[0029] This embodiment constructs a loading architecture with electro-thermal-mechanical three-field coupling and stable boundary conditions, which keeps the sample in a fixed position, fixed electrode spacing and fixed stress state throughout the test process. This reduces air gap reconstruction and electric field drift caused by unloading and re-clamping, thereby improving the comparability and repeatability of partial discharge data between different stress and temperature points.
[0030] (2) Partial discharge detection module, used to collect the partial discharge current signal of the test sample and transmit it to the main control module.
[0031] In this embodiment, the partial discharge signal is acquired by an ETS-93686 high-frequency pulse current sensor, which has a bandwidth of 10kHz to 100MHz and can cover the typical partial discharge pulse spectrum.
[0032] The process of in-situ partial discharge acquisition is as follows: Under the premise of keeping the mechanical stress constant, the electrode-sample assembly is placed in an electrothermal aging chamber, introducing a temperature field as an environmental variable for service. After reaching the target temperature, it is kept at a constant temperature for no less than 30 minutes to ensure the stability of the internal temperature distribution of the sample. Without changing the mechanical stress and temperature, a power frequency voltage is input to the experimental transformer through a voltage regulating control console, and the applied voltage is gradually increased to the partial discharge initiation voltage and stabilized at a voltage amplitude greater than the partial discharge initiation voltage. A high-frequency pulse current sensor is used to acquire the transient current signal generated by the partial discharge online. The sensor output is coupled to a high-speed digital oscilloscope through a high-voltage probe and a protective resistor, and the data is displayed and recorded in real time under the control of the main control module.
[0033] Meanwhile, in order to extract weak partial discharge signals in complex coupling environments, this embodiment adopts a "multi-stage noise reduction-statistical mapping" strategy, specifically including: Adaptive signal decomposition: Variational mode decomposition (VMD) is used to separate the partial discharge pulse from the background noise component to improve the reliability of subsequent discharge morphology parameter statistics; Specifically, baseline correction and bandpass filtering are used to preprocess the original signal, and variational mode decomposition (VMD) is further introduced as the core signal decomposition method. Compared with the uncertainty of traditional wavelet transform in the selection of wavelet basis functions and decomposition levels, and the mode mixing problem that Empirical Mode Decomposition (EMD / EEMD) is prone to, VMD decomposes non-stationary mixed signals into several mode components with limited bandwidth and well-defined center frequencies by constructing a constrained variational optimization model.
[0034] Considering the high sensitivity of VMD decomposition performance to the number of decompositions and the penalty factor, a Balanced Optimizer (EO) algorithm is further introduced to adaptively optimize key VMD parameters, enabling it to achieve optimal decomposition for partial discharge signals under different temperature, stress, and experimental noise conditions. By using indicators such as signal envelope entropy as fitness functions, the EO algorithm achieves a balance between global search and local exploitation, thereby obtaining the mode combination most conducive to preserving discharge pulse characteristics. Based on this, effective mode components containing significant discharge pulse characteristics are selected according to the kurtosis criterion for signal reconstruction, and wavelet threshold denoising is used to further remove residual white noise. This multi-level denoising and decomposition strategy significantly improves the signal-to-noise ratio while ensuring the integrity of discharge information, laying a reliable data foundation for the stable extraction of subsequent partial discharge amplitude, frequency, phase distribution, and statistical morphological parameters.
[0035] Based on the purified signal, features such as discharge peak value, number of discharges, and phase concentration are extracted to construct a phase-resolved partial discharge (PRPD) map.
[0036] The PRPD spectrum uses a complete cycle of the power frequency voltage as the time reference. Each detected discharge pulse is matched with the voltage phase at that moment to determine the specific phase position (0–360°) of the discharge within the voltage cycle. Subsequently, all discharge pulses obtained within multiple consecutive power frequency cycles are superimposed and statistically analyzed. With "phase" as the horizontal axis and "discharge amplitude or discharge intensity" as the vertical axis, a phase-resolved partial discharge (PRPD) spectrum is plotted using a scatter plot or density distribution method, thus forming a stable and repeatable discharge phase distribution characteristic.
[0037] (3) In-situ dielectric spectrum testing module, used to measure the complex dielectric constant of the test sample under stress and transmit it to the main control module.
[0038] In this embodiment, the in-situ dielectric spectrum testing module includes a precision LCR meter (electronic testing instrument, such as E4981A) or a dielectric frequency response analyzer, as well as a high-voltage relay switching unit.
[0039] The test specimen (e.g., epoxy resin / composite material) is mounted in an insulating fixture, and a preset mechanical stress is applied. While maintaining constant stress, the partial discharge test circuit is disconnected via a high-voltage relay switching unit, and an LCR meter is connected. This allows measurement of the insulation material at its characteristic frequency under this stress state. Complex permittivity at (0.1Hz - 1MHz) ;in, For the real term of the dielectric constant under stress, This is the imaginary term of the dielectric constant under stress.
[0040] (4) Surface potential decay (SPD) monitoring module, used to inject a quantitative charge into the surface of the test sample under stress, and record the decay curve of the surface potential of the test sample in situ, so as to extract the charge decay time constant related to stress and transmit it to the main control module.
[0041] To obtain trap parameters, surface charge characteristics need to be characterized during the partial discharge test gap. In this embodiment, the surface potential testing platform consists of a movable corona charging needle grid structure and a non-contact electrometer probe (KelvinProbe). While maintaining mechanical stress σ, a quantitative charge is injected onto the sample surface using the corona charging needle grid structure, and the electrometer probe is then inserted to record the surface potential. The curve of change over time is fitted using an exponential decay model in this embodiment. : ; Where A1 and τ1 describe the magnitude of the contribution of the dissipation process and its characteristic time, while V ∞ This represents the residual potential over a long timescale.
[0042] Through the Curve fitting was performed to obtain the charge decay time constant τ(σ) under different stresses.
[0043] (5) Micromorphology acquisition module, used to acquire the crack initiation and propagation path of the test specimen under stress state in real time and transmit it to the main control module.
[0044] Specifically, in-situ scanning electron microscopy (in-situ SEM) is used to observe the crack initiation and propagation paths in real time, which helps to verify changes in macroscopic electrical parameters.
[0045] (6) The main control module is used to receive data uploaded by each module and establish the physical relationship between the micromorphology, complex permittivity, charge decay time constant and partial discharge response under stress. The partial discharge detection signal is used to update the residual charge and residual field strength state of the air gap, so as to realize the accurate prediction of the evolution trend and risk state of partial discharge of insulating materials under complex service environment.
[0046] In this embodiment, the main control module, based on the received partial discharge signal, complex permittivity, charge decay time constant, and microstructure changes, analyzes the variation law between these parameters and the partial discharge response under different stresses, and establishes a physical correlation formula between the microstructure, complex permittivity, charge decay time constant, and partial discharge response under stress, as follows: ; in, This is an equivalent partial discharge intensity index obtained based on the air gap discharge mechanism, used to characterize the development trend of partial discharge; t It is used to describe the dynamic evolution of the electric field and space charge inside the air gap over time during partial discharge. The charge decay time constant is This is a correction term for the dielectric constant; This represents the equivalent partial discharge intensity index at time t under the average mechanical stress σ. The average mechanical stress applied to the test specimen. k is the scale mapping coefficient, used to map the equivalent discharge driving quantity in the air gap to the defined equivalent partial discharge intensity index; This represents the external voltage applied across the test specimen at time t. This represents the equivalent thickness of the non-air gap portion of the test sample along the electric field direction. This represents the equivalent air gap height formed or evolved under stress σ. This represents the conversion coefficient from space charge to the equivalent driving force of the air gap. It represents the amount of residual charge accumulated on the air gap wall after the i-th partial discharge (the apparent discharge amount of the partial discharge measured by the high-frequency sensor). It is characterized by the apparent charge amount of the partial discharge pulse measured by the high-frequency sensor and is used to update the residual charge state in the air gap. This represents the initial breakdown field strength related to the equivalent air gap height; Represented as the first The time point at which the partial discharge current pulse arrives at the detection port is determined by the sampling time corresponding to the first time the pulse signal in the partial discharge detection circuit exceeds the set trigger threshold.
[0047] Among them, equivalent thickness The coefficient was obtained by direct measurement using a micrometer. k and All results were obtained through fitting experiments with partial discharge.
[0048] The above physical correlation formula is a computational model established based on physical mechanisms. The partial discharge pulse correlation parameters are introduced as observations for state updates to describe the evolution of residual charge and residual field strength in the air gap. The output of the model is used to evaluate whether partial discharge under mechanical stress has a trend of continuous development and cumulative enhancement.
[0049] The above physical correlation formula uses the equivalent driving quantity (electric field or corresponding voltage drop) inside the air gap to characterize the discharge corona initiation and development process; according to Pedersen's induced charge theory, the apparent discharge quantity measured in the experiment essentially reflects the induced response of the equivalent driving quantity on the external electrode. Therefore, the apparent discharge quantity can be used to calibrate and verify the partial discharge intensity predicted by the model.
[0050] The physical correlation formula is constructed based on the air gap defect model, which assumes the actual electric field inside the air gap. E cav It consists of two parts: E cav (t)= E cap (t)+ E sc (t); in, E cap This is a capacitor voltage divider field, generated by an externally applied voltage. V app The dielectric constant and geometric dimensions of the material or air gap are determined by the material or air gap. E sc The electric field is generated by the residual charge accumulated on the air gap wall, which is the space charge.
[0051] It should be noted that the above relationship is used to describe the composition of the actual electric field inside the air gap, and whether the air gap experiences partial discharge needs to be further compared with the initial breakdown field strength. This breakdown criterion is introduced in the subsequent equivalent driving quantity model.
[0052] In order to establish the stress mapping relationship, this embodiment transforms the key parameters in the model (dielectric constant, air gap deformation, initial breakdown field strength, charge decay coefficient, etc.) into functions of stress σ.
[0053] (1) Dielectric constant correction term ε r (σ): According to experimental results, the real term of the dielectric constant exhibits a U-shaped variation with stress. This embodiment uses a polynomial to fit this relationship: ; in, This is a correction term for the dielectric constant. The average mechanical stress applied to the test specimen. , , All are fitting coefficients.
[0054] (2) Under stress The equivalent air gap height formed or evolved under the action : Mechanical stretching alters the shape of the air gap. Assuming the air gap is an ellipsoid, stretching causes it to elongate along the direction of force and contract perpendicular to it (Poisson's effect). Air gap height. d g The change (along the direction of the electric field) directly affects the partial pressure ratio. The geometric deformation term of the air gap height is as follows: ; in, It is Young's modulus. It is the effective Poisson's ratio. The coefficients are the fitted coefficients.
[0055] (3) According to Paschen's Law, the initial breakdown field strength is related to the equivalent air gap height. Specifically: ; Where E is the electric field strength and p is the gas pressure. For the critical normalized electric field, It represents the equivalent air gap height formed or evolved under stress σ.
[0056] For tiny air gaps E inc It typically decreases as the gap increases and increases as the gap decreases.
[0057] (4) Residual field strength term in the air gap discharge model : Charge decay and residual field strength τ ( σ The most critical dynamic term is the surface potential decay time constant. τ ( σ The residual electric field is determined. E sc Maintenance capacity: ; in, τ ( σ The value is obtained from the surface potential decay (SPD) monitoring module. The experimental results show that it reaches a minimum value (the fastest decay) near 10 MPa and increases under high stress.
[0058] For a single partial discharge, the residual electric field formed in the air gap can be expressed as an exponentially decaying field over time. The decay time constant is obtained from surface potential decay experiments and is related to the mechanical stress σ. Under multiple partial discharge conditions, each discharge will occur at a corresponding time... t i A residual electric field is generated, which decays over time and then superimposes at the current moment to form the total residual field strength. The initial residual field strength E generated by a single discharge is... res,0 The amount of residual charge deposited during this discharge is proportional to the amount of residual charge deposited. Introducing an equivalent mapping coefficient Φ, we obtain... Since partial discharge is a discrete event that occurs multiple times during the test, at the current time t, the total residual field strength in the air gap is the sum of the residual field strengths of each discharge, and is used as the historical discharge summation term in the final partial discharge intensity model: ; This embodiment constructs a stress-mapped expression for the partial discharge intensity based on the air gap discharge model. The dielectric parameters of the material, the geometric evolution of the air gap, and the charge decay characteristics under mechanical stress are uniformly introduced into the partial discharge model, so that the partial discharge intensity can be quantitatively calculated from the applied voltage, phase information, and stress state.
[0059] According to the expression for partial discharge intensity: ; The first term in the formula is the external capacitor voltage divider term, which describes the distribution of the applied voltage across the air gap. When σ When it reaches 10MPa, The decrease leads to a decrease in molecular (air gap partial pressure); this explains the decrease in the amplitude of partial discharge (suppression phase). When σ When >20MPa, As the pressure rises, the partial pressure in the air gap increases, leading to enhanced partial discharge.
[0060] The second term is the historical charge accumulation term, where the residual charge term describes the evolution of the residual state inside the air gap. The apparent discharge quantity is only used as an observational characterization of this state change, rather than as a direct prediction of the local discharge intensity. σ When it reaches 10 MPa, τ ( σ The value is extremely small, the exponential term rapidly approaches zero, and the residual electric field is weak, making it difficult to assist in the next corona initiation. This explains the decrease in the partial discharge repetition rate; when σ When >20 MPa, τ ( σ The increase in deep traps and the retention of residual charge contribute to the induction of seroconversion, leading to PD rebound.
[0061] The third term is the breakdown threshold term, which describes the threshold voltage required for the air gap to break down. Mechanical stretching leads to... Changes (usually microcracks opening, d g (Increases). According to the right branch of the Paschen curve, an increased gap may lead to a slight decrease or essentially no change in breakdown voltage (depending on gas pressure), but during the microcrack propagation stage, the tip effect can cause localized... E inc Significant decrease.
[0062] In practical partial discharge detection, based on the established physical correlation between microstructure, complex dielectric constant, charge decay time constant, and partial discharge response, the partial discharge intensity is calculated by acquiring the charge decay time constant, dielectric constant, applied voltage across the test sample, equivalent thickness of the non-gap portion of the test sample along the electric field direction, average mechanical stress σ applied to the test sample, equivalent partial discharge intensity index and equivalent air gap height under stress σ, residual charge accumulated on the air gap wall after partial discharge, and initial breakdown field strength. The partial discharge intensity is then compared with the initial breakdown threshold to achieve real-time prediction of the partial discharge intensity, rather than relying solely on empirical thresholds or single pulse amplitudes.
[0063] Meanwhile, based on the established physical correlation between micromorphology, complex permittivity, charge decay time constant and partial discharge response, the correlation between discharge intensity and insulation degradation rate is established by analyzing the cumulative and evolutionary changes of partial discharge intensity with time and stress, so as to evaluate the remaining lifetime of insulating materials under non-uniform electric field and mechanical stress coupling conditions.
[0064] The method in this embodiment solves the problems in the prior art that it is impossible to uniformly quantify the intensity of partial discharge under different stress conditions, it is difficult to accurately predict the discharge development trend, and the insulation life assessment is unreliable. It significantly improves the comparability, predictability and practicality of partial discharge detection results in engineering applications.
[0065] Experimental verification: The main raw materials for preparing the samples were: bisphenol A type epoxy resin (BADGE, E51), 4,4′-diaminodiphenyl disulfide (AFD), and 4,4′-diaminodiphenylmethane (MDA). The epoxy resin preparation process was as follows: BADGE was mixed with AFD or MDA in a certain proportion to ensure that the ratio of amino active hydrogen content to epoxy group content was 1:1, and an initial crosslinking mixture was obtained. After stirring evenly at 50°C, the mixture was poured into a mold and placed in a vacuum drying oven for 60 min to eliminate air bubbles. It was then pre-cured at 80°C for 2 h at a pressure of 0.5 MPa and cured at 150°C for 3 h at a pressure of 2 MPa, finally obtaining EP-AFD and EP-MDA film samples with a thickness of about 0.1 mm.
[0066] To illustrate the non-monotonic effect of stress on partial discharge and dielectric properties measured in the experiment, the partial discharge intensity detection experimental system for insulating materials under non-uniform electric field in this embodiment was used to test and analyze the partial discharge of samples at different stress levels (0-20MPa) and different temperatures (20-70℃).
[0067] like Figure 3As shown in (a) and (b), the partial discharge amplitude and discharge number of both EP-AFD and EP-MDA at different temperatures exhibit an "inflection point" characteristic, first decreasing and then increasing with stress, reaching a minimum around 10 MPa. This pattern remains consistent across different temperatures; the discharge amplitude increases with increasing temperature, indicating that thermal excitation promotes carrier migration and air gap ionization. The discharge amplitude of EP-AFD is generally lower than that of EP-MDA, suggesting that the disulfide bond network facilitates carrier transport and trap control, thereby suppressing partial discharge activity. Skewness and kurtosis analysis of the discharge amplitude distribution are shown below. Figure 4 As shown, except for EP-MDA at 70℃, the other samples all showed a trend of first increasing and then decreasing with increasing stress.
[0068] Figure 5 (a)-(c) in the figure show the PRPD spectra of EP-AFD at 20℃ and 0 MPa, 20℃ and 10 MPa, and 20℃ and 20 MPa, respectively. Figure 6 (a)-(c) in the figure are the PRPD spectra of EP-AFD at 70℃ and 0 MPa, 70℃ and 10 MPa, and 70℃ and 20 MPa, respectively. Figure 7 (a)-(c) in the figure show the PRPD spectra of EP-MDA at 20℃ and 0 MPa, 20℃ and 10 MPa, and 20℃ and 20 MPa, respectively. Figure 8 Figures (a)-(c) show the PRPD spectra of EP-MDA at 70℃ and 0 MPa, 70℃ and 10 MPa, and 70℃ and 20 MPa, respectively. As can be seen from the figures, at 10 MPa, the discharge clusters are concentrated at small amplitudes, and the distribution concentration increases; when the stress further increases to 20 MPa, the distribution tends to flatten, and large-amplitude discharge events increase. Partial discharge under the ball-plate electrode mainly occurs in the air gap between the electrode and the epoxy material surface. The interface morphology and accumulated charge state of the epoxy affect the synthetic electric field within the air gap, thus altering the discharge characteristics. The discharge amplitude and number of EP-AFD events significantly decrease under 10 MPa tension, while the discharge activity increases at 20 MPa, indicating that mechanical stress has a non-monotonic modulating effect on partial discharge behavior.
[0069] Figure 9 In-situ SEM microstructure images under different stresses are presented. It can be seen that the surface is relatively flat and smooth when there is no stress, with only a small number of original curing shrinkage micro-traces. When the stress increases to 10 MPa, a small number of nanoscale dispersed microcracks appear, but the distribution is relatively uniform. High magnification images show that the cracks have low contrast and shallow depth.
[0070] Studies have shown that glassy epoxy typically exhibits a near-linear response only within a very small strain range under quasi-static tensile conditions at room temperature. Subsequently, viscoelastic nonlinearity and microscale damage may occur with increasing strain. The appearance of nanoscale shallow cracks at 10 MPa (approximately 0.78% strain) indicates that the material is in the transition range from near-linear elasticity to damage, and microscale damage begins to appear. Further increasing the strain to 20 MPa, the cracks significantly extend and partially penetrate, forming a network crack structure with local connections. The crack width increases to approximately 100-300 nm, and both surface undulation and roughness increase significantly. At this point, the material has entered the damage stage of crack development. The generation and connection of these cracks will change the local dielectric constant distribution and surface electric field intensity, affecting carrier injection and partial discharge activities. When stretched to 60 MPa, the material enters the fracture initiation stage, with surface cracks deepening to the μm level and exhibiting a layered structure. Cracks are dense near the fracture surface and sparser further away, reflecting typical stress concentration and microcrack evolution characteristics.
[0071] Figures 10-11 The test results of dielectric constant and dielectric loss factor of EP-AFD and EP-MDA under different stresses are given respectively. It can be seen that in the range of 100Hz-1MHz, the dielectric constant and dielectric loss factor both show a trend of first decreasing and then increasing with the increase of mechanical stress, and have a minimum value at 10MPa.
[0072] Figure 12 and Figure 13 The surface potential changes of EP-AFD and EP-MDA under different stresses are presented respectively. It can be seen that when tension is applied, the surface potential decreases significantly faster, with the fastest decrease at 10 MPa and the second fastest at 20 MPa.
[0073] Based on the above experimental results, overall, mechanical stress has a phased impact on the electrical behavior of epoxy materials. Figure 14 A schematic diagram illustrating the evolution of material structure with increasing mechanical stress and its impact on electrical properties is presented. This mechanism can be divided into two stages: (1) Chain segment orientation-free volume dominance stage (low stress region, (≤10MPa): When the tensile stress increases from 0 to about 10 MPa, the epoxy network structure mainly undergoes ordered orientation of molecular chain segments and moderate expansion of free volume. The stretch-induced chain segment orientation weakens the relaxation / orientation polarization of epoxy, and the dielectric constant and dielectric loss decrease simultaneously. At the same time, stretching increases the free volume of the material and introduces shallower local potential wells / traps, which is conducive to the short-range transition and recapture-release process of charge carriers, thereby increasing the apparent bulk conductivity.
[0074] like Figure 15In the spherical electrode structure shown, the three-point junction region of the spherical electrode, air gap, and epoxy material exhibits a non-uniformly distributed electric field. Partial discharge mainly occurs at the air gap between the spherical electrode and the surface of the insulating material. When a tensile strength ≤10 MPa is applied, the relative permittivity of the material decreases while the bulk conductivity increases. Due to the difference in electrical parameters between the epoxy layer and the air layer, the electric field in the air gap weakens, suppressing the generation of partial discharge. Furthermore, due to the periodic reversal characteristic of the electric field under power frequency sinusoidal voltage excitation, surface charges of uniform polarity remain on the material surface after partial discharge, such as... Figure 16 As shown, the combined electric field strength in the air gap increases after the polarity change, which promotes the generation of partial discharge. The surface potential dissipation experiment at 10 MPa shows that the surface charge decay rate is significantly accelerated, which weakens the electric field during the polarity reversal and further reduces the discharge trigger probability. This explains the phenomenon that the amplitude and number of partial discharges decrease at 10 MPa.
[0075] (2) Microcrack-interface polarization-dominated stage (high stress region, approximately 20 MPa): When the tensile stress further increases to 20 MPa, the material enters the structural damage-dominated stage. In-situ SEM results show that the width and depth of microcracks on the epoxy surface increase to hundreds of nanometers to several micrometers, and some cracks are interconnected to form a network of through-holes. These cracks are equivalent to introducing pointed defects and air gaps with low dielectric constants into the material, significantly enhancing the local electric field concentration effect. Figure 17 and Figure 18 Simulation results show that in the ball-plate electrode structure, the electric field intensity along the material surface near the crack region (black box region) increases significantly, with a maximum increase of approximately 17%. The electric field distortion is concentrated at the defect tip, and the local electric field is more likely to reach the partial discharge initiation voltage. Simultaneously, the appearance of cracks and interface polarization regions under high stress interrupts the charge transport path, causing space charges to be recaptured or undergo localized directional migration at the defect interface, increasing surface charge retention and electric field distortion compared to low stress. These factors collectively lead to a deterioration in discharge characteristics, reflected in the presence of more large-amplitude discharge points and a denser phase distribution in the PRPD spectrum.
[0076] In summary, appropriate mechanical prestress can effectively suppress partial discharge behavior by regulating the internal polarization behavior, space charge accumulation, and surface charge dissipation of the material. However, excessive stress leads to enhanced partial discharge activity due to structural damage and local electric field distortion, revealing the critical response behavior of epoxy insulation systems under the mechanical-electric coupling mechanism.
[0077] Example 2 In one or more embodiments, an experimental method for detecting the partial discharge intensity of insulating materials under a non-uniform electric field is disclosed, combined with... Figure 2 Specifically, it includes: A controllable tensile or compressive stress is applied to the test specimen, and an electric field and a temperature field are introduced simultaneously to put the test specimen in a stable and reproducible force-thermal-electric coupling constraint state. The complex permittivity, surface potential decay curve, crack initiation and propagation path, and partial discharge current signal of the test specimen under stress were measured respectively to establish the physical relationship between microstructure, complex permittivity, charge decay time constant and partial discharge response under stress. Based on the aforementioned physical correlation, accurate prediction of the partial discharge risk of insulating material test samples under complex service environments can be achieved.
[0078] As a further approach, in the actual partial discharge detection process, based on the established physical correlation between micromorphology, complex dielectric constant, charge decay time constant and partial discharge response, the partial discharge intensity is calculated by obtaining the charge decay time constant, dielectric constant, applied voltage across the test sample, equivalent thickness of the non-gap portion of the test sample along the electric field direction, average mechanical stress σ applied to the test sample, equivalent partial discharge intensity index and equivalent air gap height under stress σ, residual charge accumulated on the air gap wall after partial discharge and initial breakdown field strength. Based on the established physical correlation between microstructure, complex permittivity, charge decay time constant and partial discharge response, the correlation between discharge intensity and insulation degradation rate is established by analyzing the cumulative and evolutionary changes of partial discharge intensity with time and stress, so as to evaluate the remaining lifetime of insulating materials under non-uniform electric field and mechanical stress coupling conditions.
[0079] It should be noted that the specific implementation method of the above process is exactly the same as that in Example 1, and will not be described in detail again.
[0080] While the specific embodiments of the present invention have been described above in conjunction with the accompanying drawings, this is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art without creative effort based on the technical solutions of the present invention are still within the scope of protection of the present invention.
Claims
1. An experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field, characterized in that, include: The three-field coupling loading module is used to apply controllable tensile or compressive stress to the test specimen and simultaneously introduce electric and temperature fields to put the test specimen in a stable and reproducible force-thermal-electric coupling constraint state. The partial discharge detection module is used to collect the partial discharge current signal of the test sample to characterize the occurrence time and intensity characteristics of the partial discharge event, and transmit it to the main control module. The in-situ dielectric spectroscopy testing module is used to measure the complex dielectric constant of the test sample under stress and transmit it to the main control module. The surface potential decay monitoring module is used to inject a quantitative charge into the surface of the test sample under stress and record the decay curve of the surface potential of the test sample in situ to extract the stress-related charge decay time constant and transmit it to the main control module. The micromorphology acquisition module is used to acquire the crack initiation and propagation path of the test specimen under stress in real time and transmit it to the main control module. The main control module is used to receive data uploaded by each module and establish the physical correlation between microstructure, complex dielectric constant, charge decay time constant and partial discharge response under stress, so as to achieve accurate prediction of the partial discharge risk of insulating materials in complex service environments.
2. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 1, characterized in that, The three-field coupling loading module specifically includes: The mechanical loading unit includes insulating clamps for holding both ends of the test specimen, and a push-pull force gauge connected to at least one insulating clamp; the push-pull force gauge applies in-situ mechanical tensile or compressive stress to the test specimen to simulate the residual or service stress state of the test specimen in actual equipment caused by structural constraints, curing shrinkage or operating loads. Temperature control unit, including an electrothermal aging chamber, is used to provide a preset temperature environment for the test sample; The electric field generating unit includes ball-plate electrodes respectively disposed on the upper and lower end faces of the test specimen, which are used to provide a controllable non-uniform electric field for the test specimen.
3. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 2, characterized in that, The load value is read in real time by a push-pull force gauge, and the corresponding average mechanical stress is calculated by combining it with the effective force-bearing cross-sectional area of the test specimen. ; Where F is the mechanical stress, i.e. the load value of the push-pull force gauge; S is the cross-sectional area of the material.
4. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 2, characterized in that, The main control module performs adaptive signal decomposition on the received partial discharge current signal to separate the effective partial discharge components; based on the effective partial discharge components, it extracts the discharge peak value, number of discharges and phase concentration parameters to construct a phase-resolved partial discharge map to obtain the phase distribution characteristics of the partial discharge.
5. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 1, characterized in that, The main control module establishes the physical relationship between microstructure, complex permittivity, charge decay time constant, and partial discharge response, specifically as follows: ; in, The charge decay time constant is This is a correction term for the dielectric constant; This represents the equivalent partial discharge intensity index at time t under the average mechanical stress σ. The average mechanical stress applied to the test specimen. k These are the scale mapping coefficients. This represents the external voltage applied across the test specimen at time t. This represents the equivalent thickness of the non-air gap portion of the test sample along the electric field direction. σ represents the equivalent air gap height formed or evolved under stress σ, and Φ represents the proportionality coefficient that converts the cumulative effect of residual charge into the equivalent partial discharge driving quantity. This represents the amount of residual charge accumulated on the air gap wall after the i-th partial discharge. Represented as the first The time point at which the partial discharge current pulse arrives at the detection port. This represents the initial breakdown field strength related to the equivalent air gap height.
6. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 5, characterized in that, The dielectric constant correction term is obtained by fitting the correspondence between the real part of the complex dielectric constant and the stress, specifically: ; in, This is a correction term for the dielectric constant. The average mechanical stress applied to the test specimen. , , All are fitting coefficients.
7. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 5, characterized in that, Under stress The equivalent air gap height formed or evolved under the action Specifically: ; in, It is Young's modulus. It is the effective Poisson's ratio. The coefficients are the fitted coefficients.
8. The experimental system for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 5, characterized in that, Initial breakdown field strength related to equivalent air gap height Specifically: ; Where E is the electric field strength and p is the gas pressure. For the critical normalized electric field, It represents the equivalent air gap height formed or evolved under stress σ.
9. A method for detecting the partial discharge intensity of insulating materials under a non-uniform electric field, characterized in that, include: A controllable tensile or compressive stress is applied to the test specimen, and an electric field and a temperature field are introduced simultaneously to put the test specimen in a stable and reproducible force-thermal-electric coupling constraint state. The complex permittivity, surface potential decay curve, crack initiation and propagation path, and partial discharge current signal of the test specimen under stress were measured respectively to establish the physical relationship between microstructure, complex permittivity, charge decay time constant and partial discharge response under stress. Based on the aforementioned physical correlation, accurate prediction of the partial discharge risk of insulating material test samples under complex service environments can be achieved.
10. The experimental method for detecting partial discharge intensity of insulating materials under a non-uniform electric field as described in claim 9, characterized in that, In the actual partial discharge detection process, based on the established physical correlation between micromorphology, complex dielectric constant, charge decay time constant and partial discharge response, the partial discharge intensity is calculated by obtaining the charge decay time constant, dielectric constant, applied voltage across the test sample, equivalent thickness of the non-gap portion of the test sample along the electric field direction, average mechanical stress σ applied to the test sample, equivalent partial discharge intensity index and equivalent air gap height under stress σ, residual charge accumulated on the air gap wall after partial discharge and initial breakdown field strength. Based on the established physical correlation between microstructure, complex permittivity, charge decay time constant and partial discharge response, the correlation between discharge intensity and insulation degradation rate is established by analyzing the cumulative and evolutionary changes of partial discharge intensity with time and stress, so as to evaluate the remaining lifetime of insulating materials under non-uniform electric field and mechanical stress coupling conditions.